Consumption of Energy, Protein, Iron and Knowledge the Incidence of Chronic Energy Deficiency (KEK) Pregnant Women in the Labuan : Konsumsi Energi, Protein, Zat Besi dan Pengetahuan terhadap Kejadian Kekurangan Energi Kronik (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Labuan - Rutni Tomeys; Ni Ketut Kariani; Masfufah (Politeknik Karya Persada Muna, 2022)
Baground: Based on the basic health research (Riskesdas) the prevalence of KEK cases in pregnant women in Indonesia is 17.3%. It occurs in all age groups and conditions of women (pregnant and non pregnant.Central Sulawesi had a SEZ prevalence in 2018 of 22.7%. The purpose of this study was to analyze the relationship between energy consumption, protein, iron, and knowledge on the incidence of Chronic Energy Deficiency (KEK) in pregnant women in the working area of ​​the Labuan.Method: The research design is quantitative with a cross sectional study design.This research was conducted in August 2022 in the Labuan Health Center Work Area. The population of this study were mothers who visited Labuan Health Center as many as 348 people. The sample is 44 people, with the sampling technique of cluster sampling. The research instruments are LILA measurement, food recall, Semi quantitative Food Frequency questionnaire (SQ-FFQ) and knowledge questionnaire. Analysis using chi-square test.Results: Based on the results of the study, there was a relationship between energy consumption of 0.064, protein 0.003, iron 0.044, and knowledge of 0.048 with the incidence of KEK in pregnant women in the working area of the Labuan Health Center.Conclusions:Insufficient income, inadequate sources of protein in the body, lack of interest from residents to come during socialization, less intake of respondents than needs, small portions of food and less diverse food menus obtained during a 2x24 hour recall resulted in many respondents experiencing SEZ.Suggestion: This research can be used as a source of education to help respondents increase their intake of energy, protein, iron, and knowledge to reduce the risk of CED in pregnant women.Keywords: Energy, protein, iron, knowledge, and KEK